2007
DOI: 10.1590/s0103-50532007000700011
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of glyceride esters in solvent-free system: influence of the molar ratio, lipase source and functional activating agent of the support

Abstract: Este trabalho avaliou a influência de fatores que afetam a síntese de ésteres glicéricos, tais como: razão molar entre os reagentes, fonte de lipase e tipo de agente de ativação do suporte obtido pela técnica sol-gel. Foram empregadas preparações comerciais de lipases imobilizadas em partículas de polissiloxano-álcool polivinílico (POS-PVA) previamente ativadas com diferentes agentes (glutaraldeído, metaperiodato de sódio e carbonildiimidazol). Esses resultados foram comparados com aqueles obtidos por preparaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 22 publications
(38 reference statements)
1
21
0
12
Order By: Relevance
“…However, as Lipozyme 435 is a type of immobilized lipase that already has a certain content of water, and it can maintain activity without the addition of extra water (Zhong et al, 2013). On the contrary, the addition of extra water reduced the enzyme concentration and affected the hydration of the enzyme directly, or indirectly, by changing the nature of lipase support materials (Freitas et al, 2007), which resulted in a decrease in enzyme activity. On the other hand, esterification is the reverse reaction of hydrolysis.…”
Section: Effect Of Water Contentmentioning
confidence: 99%
“…However, as Lipozyme 435 is a type of immobilized lipase that already has a certain content of water, and it can maintain activity without the addition of extra water (Zhong et al, 2013). On the contrary, the addition of extra water reduced the enzyme concentration and affected the hydration of the enzyme directly, or indirectly, by changing the nature of lipase support materials (Freitas et al, 2007), which resulted in a decrease in enzyme activity. On the other hand, esterification is the reverse reaction of hydrolysis.…”
Section: Effect Of Water Contentmentioning
confidence: 99%
“…When the production of a high degree pure monoglyceride is desired, lipase-catalyzed esterification is the appropriate route. Lipase-catalyzed synthesis of these partial glycerols by the direct esterification of glycerol with fatty acids in different reaction media have been studied and concluded that aqueous-organic two-phase systems [25], microemulsions [26,27] and anhydrous organic solvents [27] as well as the use of solvent-free systems are the best selections [28,29]. Apart from solvent system, proper selection of lipase also contributes to success of the method.…”
Section: Enzymatic Glycerolysis and Liquid Catalyzationmentioning
confidence: 99%
“…3.1.1.3) provenientes do fungo Thermomyces lanuginosus, comercializadas sob a denominação de Lipozyme TL, tem sido citada em diversos trabalhos relacionados à obtenção de ésteres. 1,2,[6][7][8][9][10][11][12][13] Na sua forma imobilizada, estas enzimas são mais estáveis no meio orgânico, facilitando sua recuperação e posterior reutilização. 8 Dessa forma, ainda existe um grande campo de estudos a ser explorado, relacionado à síntese enzimática de ésteres em sistemas que empreguem materiais de baixo custo como suportes, gerando resultados que permitam avaliar a viabilidade técnica econômica da produção desses compostos.…”
Section: Introductionunclassified